Smart-technologies in the modern economy - Klevan, A. D.; Pererva, P. G. (My University, 2023)
It has been proven that the introduction of an innovative and technological type of development, knowledge becomes the main intangible asset, affecting the growth of production volumes, improving the quality of products and services, ensuring the country's competitiveness and accelerating social progress.
Smart-технології в сучасній економіці
Keywords: business; production activity; smart technologies; efficiency